2018
DOI: 10.1177/1687814018767487
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of single-stage air source heat pump utilizing indirect vapor injection design

Abstract: This study investigated the performance of a single-stage scroll compressed air source heat pump coupled with a flash tank indirect vapor injection. In the refrigerant circulating piping of the heat pump, an indirect vapor injection piping connecting a flash tank at the refrigerant outlet of a condenser and the suction of a scroll compressor was designed. By the indirect refrigerant vapor injection from the flash tank, the saturation pressure and temperature of the refrigerant (R134a) in the evaporator can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Regarding the heat recovery and thermal storage in the heat pump system, the wasted heat ejected from condenser of an air conditioner can be recovered and be used to generate hot water. In the past 70 years, several studies have found that high-performance heat pumps can be employed to achieve energy savings [6][7][8][9][10]. However, these studies have mainly focused on energy savings in terms of the hot water supply.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the heat recovery and thermal storage in the heat pump system, the wasted heat ejected from condenser of an air conditioner can be recovered and be used to generate hot water. In the past 70 years, several studies have found that high-performance heat pumps can be employed to achieve energy savings [6][7][8][9][10]. However, these studies have mainly focused on energy savings in terms of the hot water supply.…”
Section: Introductionmentioning
confidence: 99%
“…They theoretically showed that increasing the vapor injection pressure increases the amount of vapor injection and the subcooling degree of the refrigeration cycle and enhances the performance of the system. Luo and coworkers (19,20) developed an intelligent strategy for controlling the subcooling degree by sensing the condensation temperature and subcooled refrigerant temperature at the inlet of the expansion valve to dynamically obtain high performance of a heat pump at different condensation temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a vapor compression heat pump system has high efficiency and is considered to be competitive to decrease energy consumption and thus reduce CO 2 emission [5,6]. Continuous efforts with regard to research on more efficient systems have mainly focused on viewpoints using alterative cycles [7][8][9][10] and the use of new refrigerants [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, heat pump systems with vapor injection to the suction port of a single-stage compressor have been recommended as a relatively inexpensive solution for vapor injection heat pump system. Lai et al [10] developed a single-stage air source heat pump with indirect vapor injection piping connecting a flash tank at the refrigerant outlet of the condenser and the accumulator of a scroll compressor. They concluded that the COP increments of 5-15% had been obtained when the heat pump was operated under ambient temperatures ranging from 5 • C to 35 • C. Roh and Kim [13] proposed a novel vapor injection cycle by injecting vapor refrigerant into the accumulator instead of the injection port of compressor.…”
Section: Introductionmentioning
confidence: 99%